Advancing Socioeconomic Development through Equitable Higher Education Administration in Nigeria - NWANKWO, FRANCA; CHIJIOKE, IWEHA CHRIS (American Journal of STEM Education, 2024)
This paper discusses the critical importance of equity in higher education administration as a lever for societal advancement. It posits that the persistent inequalities within Nigerian higher education stemming from religion, gender, ethnicity, and socioeconomic disparities have hindered the realization of the nation’s full potential. This paper explores how these systemic inequities have led to unrest and disrupted educational environments, ultimately impacting the quality of graduates and the country’s economic trajectory. The study argues for a strategic approach to fostering equity, which involves inclusive admission policies, fair hiring practices, and the creation of an inclusive campus climate. It emphasizes the role of leadership in advocating for and implementing these changes. This paper also outlines how the equitable administration of higher education in Nigeria can serve as a catalyst for sustained socioeconomic development, drive growth, and foster social cohesion in countries rich in diversity but plagued by divisions. In conclusion, this paper underscores the necessity of a multifaceted strategy that includes policy reform, capacity building, and cultural competency training to promote equity in Nigerian higher education.